2021
DOI: 10.1111/poms.13485
|View full text |Cite
|
Sign up to set email alerts
|

Incentivizing Farmers to Invest in Quality through Quality‐Based Payment

Abstract: We consider a for‐profit cooperative that sets a quality‐based payment to its risk‐averse farmers in order to incentivize them to invest in quality improvements. The quality of the farmer's harvest is affected by his investments during the growing season. To satisfy both the farmer and the cooperative, the payment must be competitive with the open‐market prices. Cooperatives often set payments that mimic the open‐market prices; however, this practice fails to incentivize farmers to invest in quality. Our work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Zhao et al (2021) found that internal and external supply chain integration are the key factors to improve product quality. Ayvaz-cavdaroglu et al (2021) explored how a quality-based payment approach (with market prices) to incentivize farmers to improve quality. They found that this approach, combined with crop insurance, could achieve meaningful gains.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhao et al (2021) found that internal and external supply chain integration are the key factors to improve product quality. Ayvaz-cavdaroglu et al (2021) explored how a quality-based payment approach (with market prices) to incentivize farmers to improve quality. They found that this approach, combined with crop insurance, could achieve meaningful gains.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studying a setting where farmers are exposed to yield, quality, and market price uncertainties, Ayvaz‐Çavdaroğlu et al. (2021) show that the farmers underinvest in the crop quality when they are compensated based on the market price. Levi et al.…”
Section: Agriculturementioning
confidence: 99%
“…Historically, in a cooperative, there are no differentiated payments according to quality, but instead a payment based on a pooling price received by cooperatives on the market (Liang & Hendrikse, 2016). However, in recent years, an increasing number of cooperatives have used incentive payments (Ayvaz‐Cavdaroğlu et al, 2021). This practice is generally used by large agricultural cooperatives, but these contracts have clearly been widely adopted by the cooperative movement.…”
Section: Introductionmentioning
confidence: 99%
“…Incentive through quality will bring about among members competition on investment in quality. This investment aims to capture the quality premium paid by the cooperative, which is perceived as a return on investment (Ayvaz‐Cavdaroğlu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%